Evaluation of the Viability and Vigor of Karya Pelalawan Rice Seeds (Oryza sativa L.) Under Salt Stress Conditions - Mardiani Putri; Yudia Azmi; Salmiyati Salmiyati (Open Global Scientific Journal, 2026)
Background: One of the well-known rice varieties from Pelalawan is the Karya Pelalawan rice, which can be developed in tidal swamp lands in Riau Province. The tidal lands of Pelalawan Regency frequently experience variable salinity levels, yet the salinity tolerance of the Karya Pelalawan rice variety remains poorly defined. Consequently, it is necessary to conduct tests across diverse salinity concentrations. Aims: This research aims to identify the tolerant concentration of NaCl in the salinity test on the viability and vigor of rice seeds (Oryza sativa L.) of the Karya Pelalawan variety.Methods: The study employed a non-factorial Completely Randomized Design (CRD) consisting of 5 treatments with 5 replications. The treatments were as follows: P0 (0 ppm), P1 (2500 ppm), P2 (5000 ppm), P3 (7500 ppm), and P4 (10000 ppm). The observed parameters included germination percentage, first count test (FCT) percentage, germination rate, radicle and plumule growth of seedlings, and seed vigor test. Data were analyzed using Excel and ANOVA, followed by the DMRT at 5% significance level.Results: The results showed that NaCl application affected the germination percentage, FCT percentage, germination rate, radicle and plumule growth, and seed vigor. The tolerant NaCl concentration for germination was P1 (2,500 ppm) as seen from the germination percentage, FCT percentage, germination rate, and seed vigor.Conclusion: The application of salinity stress can affect germination characteristics. However, at 2500 ppm, it can improve the germination quality of Karya Pelalawan rice seeds.